1989
DOI: 10.1530/acta.0.1200099
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thyrotropin-stimulated adenylate cyclase activation and growth of rat thyroid cells, FRTL-5, by immunoglobulin G from patients with primary myxedema: comparison with activities of thyrotropin-binding inhibitor immunoglobulins

Abstract: Abstract. We studied the blocking type TSH receptor antibodies in 28 patients with primary myxedema and 21 patients with goitrous Hashimoto's thyroiditis by measuring the ability of their IgGs to inhibit TSH binding to its receptor, and to inhibit TSH-stimulated cAMP increase and [3H] thymidine incorporation in a rat thyroid cell line, FRTL-5. The incidences of TSH binding inhibitor immunoglobulin, thyroid stimulation inhibiting immunoglobulin and thyroid growth inhibiting immunoglobulin in patients with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…No speci®c distribution pattern could be established. Thyroid function-blocking antibodies are found in up to 75% of patients with primary myxoedema, the atrophic form of auto-immune thyroiditis, but not in healthy adults or patients with hypertrophic Hashimoto thyroiditis [2,7,16]. Considering this, the percentage of children with increased TBAb is high in our study population.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…No speci®c distribution pattern could be established. Thyroid function-blocking antibodies are found in up to 75% of patients with primary myxoedema, the atrophic form of auto-immune thyroiditis, but not in healthy adults or patients with hypertrophic Hashimoto thyroiditis [2,7,16]. Considering this, the percentage of children with increased TBAb is high in our study population.…”
Section: Discussionmentioning
confidence: 64%
“…Increased TSH receptor antibodies (TRAb) are often associated with Graves disease; their presence is indicative of auto-immune hyperthyroidism. TSH function-blocking antibodies (TBAb) and cytotoxic antibodies (CAb) can be found in all types of auto-immune thyroid disease in all age groups but predominate in the atrophic form of Hashimoto thyroiditis [2,3,7,16].…”
Section: Introductionmentioning
confidence: 99%
“…[11,14] in autoimmune thyroid disease, respectively. Tamai et al [3] reported that TSBAb might account for hypothyroidism in approximately one third of cases of Graves' disease previously treated with ATDs, and the remaining two thirds might be due to autoimmune thyroiditis.…”
Section: Case Report and Resultsmentioning
confidence: 99%
“…These blocking antibodies (TSBAbs) compete with TSH for receptor binding and block the biological effects of TSH on thyroid cells, including cAMP production, iodine uptake, and thyroid cell growth (26)(27)(28). They induce transient neonatal hypothyroidism when transferred across the placenta (29,30).…”
Section: Thyroid Stimulation Blocking Antibody Assaymentioning
confidence: 99%
“…They induce transient neonatal hypothyroidism when transferred across the placenta (29,30). TSBAb assay quantitates inhibition by autoantibodies of the increase in cAMP production or the iodide uptake in response to a standard concentration of TSH in the FRTL-5 cell (26)(27)(28) or CHO-TSHR cell (31,32).…”
Section: Thyroid Stimulation Blocking Antibody Assaymentioning
confidence: 99%